Electrode material, negative electrode body, and non-aqueous lithium ion secondary battery

By coating silicon-based particles in lithium-ion batteries with a cationic polymer containing a fluorine-containing anion, the inefficiencies in charging and discharging are addressed, leading to improved battery performance and efficiency.

JP7658312B2Active Publication Date: 2025-04-08TOYOTA JIDOSHA KK
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022042756
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-03-17
Publication Date
2025-04-08
Estimated Expiration
2042-03-17

AI Technical Summary

Technical Problem

Existing lithium-ion batteries face inefficiencies in charging and discharging due to the collapse of protective layers on silicon-based particles, leading to exposure and decomposition by the electrolyte.

Method used

The use of silicon-based particles coated with a cationic polymer having a fluorine-containing anion as counter anion, which maintains a positive zeta potential and effectively prevents the collapse of the coating layer during charge and discharge cycles.

Benefits of technology

This approach enhances the charging and discharging efficiency of lithium-ion batteries by preventing the exposure of silicon particles to the electrolyte, thus maintaining battery performance even after repeated cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658312000002
    Figure 0007658312000002
  • Figure 0007658312000001
    Figure 0007658312000001
Patent Text Reader

Abstract

To provide an electrode material capable of improving battery charging and discharging efficiency, a negative electrode body, and a nonaqueous lithium ion secondary battery.SOLUTION: A disclosed electrode material contains a silicone-active material in which silicone particles are at least partially coated with a cationic polymer, and the cationic polymer has a fluorine-containing anion as a counter-anion. A disclosed negative electrode body contains the disclosed electrode material. A disclosed nonaqueous lithium ion secondary battery includes the positive electrode body, the separator, and an electrode material according to aspect 8 that are housed in this order in a battery case filled with electrolyte.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an electrode material, a negative electrode body, and a non-aqueous lithium-ion secondary battery.

Background Art

[0002] Patent Document 1 discloses a composite comprising a silicon material, a carbon layer covering the silicon material, and a cationic polymer layer having a cationic polymer covering the carbon layer.

[0003] Patent Document 2 discloses a negative electrode material for a lithium storage battery, which includes a core containing silicon, and the surface of the core has an O y SiH x group (where 1 < x < 3, 1 ≤ y ≤ 3, and x > y), and the material has a positive zeta potential within the range of pH 3.5 to 9.5.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Patent Document 2

Summary of the Invention

Problems to be Solved by the Invention

[0005] There is a demand to improve the charge and discharge efficiency of batteries, such as lithium-ion batteries.

[0006] An object of the present disclosure is to provide an electrode material, a negative electrode body, and a non-aqueous lithium-ion secondary battery capable of improving the charge and discharge efficiency of a battery.

Means for Solving the Problems

[0007] The present inventors have found that the above object can be achieved by the following means: Aspect 1 The silicon-based active material includes silicon-based particles at least partially coated with a cationic polymer, The cationic polymer has a fluorine-containing anion as a counter anion. electrode material. Aspect 2 2. The electrode material according to claim 1, wherein the silicon-based active material has a positive zeta potential in water. Aspect 3 3. The electrode material according to claim 1 or 2, wherein the silicon-based particles are Si particles or Si alloy particles. Aspect 4 The electrode material according to any one of aspects 1 to 3, wherein the cationic polymer is at least one selected from the group consisting of poly(diallyl dimethyl chloride), a copolymer of poly(diallyl dimethyl chloride) and another polymer, and an anion exchange resin, in which all or a part of the counter anion is exchanged with the fluorine-containing anion. Aspect 5 5. The electrode material according to any one of aspects 1 to 4, wherein the fluorine-containing anion is an imide-based anion. Aspect 6 6. The electrode material according to any one of aspects 1 to 5, further comprising an anionic binder. Aspect 7 7. The electrode material according to claim 6, wherein the anionic binder is at least one selected from the group including polyacrylic acid, carboxymethyl cellulose, polystyrene sulfonic acid, and poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate). Aspect 8 A negative electrode body comprising the electrode material according to any one of the first to seventh aspects. Aspect 9: A non-aqueous lithium ion secondary battery comprising a positive electrode body, a separator, and the negative electrode body according to embodiment 8 housed in this order in a battery case filled with an electrolyte. Effect of the Invention

[0008] According to the present disclosure, it is possible to provide an electrode material, a negative electrode assembly, and a nonaqueous lithium ion secondary battery that can improve the charge / discharge efficiency of a battery. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic diagram of a nonaqueous lithium-ion secondary battery 100 according to a first embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the present disclosure will be described in detail. Note that the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the present disclosure.

[0011] 《Electrode material》 The electrode material of the present disclosure is an electrode material that contains a silicon-based active material in which silicon-based particles are at least partially coated with a cationic polymer, and the cationic polymer has a fluorine-containing anion as a counter anion.

[0012] In batteries, such as lithium ion batteries, silicon-based particles may be used as an active material, such as a negative electrode active material. For example, in non-aqueous lithium ion secondary batteries, the surface of the silicon particles may be covered with a protective layer, such as a layer of inorganic particles, in order to suppress the formation of SEI between the silicon-based particles and the electrolyte.

[0013] However, since silicon particles expand and contract as they absorb and release charge carriers, such as lithium ions, during charging and discharging of the battery, the layer of inorganic particles, which has low elasticity, is prone to collapse during charging and discharging of the battery.

[0014] When the layer of inorganic particles collapses and the silicon particles are exposed to the electrolyte, the electrolyte is likely to decompose in that area. Therefore, a battery using silicon-based particles coated with a layer of inorganic particles as an active material, for example, a negative electrode active material, does not have sufficient charge / discharge efficiency.

[0015] In contrast, the electrode material of the present disclosure contains a silicon-based active material in which silicon-based particles are at least partially coated with a cationic polymer, and the cationic polymer has a fluorine-containing anion as a counter anion.

[0016] The silicon-based particles have a negative zeta potential in the electrolyte. On the other hand, the cationic polymer has a positive zeta potential in the electrolyte. Therefore, in a silicon-based active material in which the silicon-based particles are at least partially covered with a cationic polymer, the cationic polymer having elasticity can follow the expansion and contraction of the silicon-based particles accompanying the charging and discharging of the battery due to the electrostatic interaction between the negatively charged silicon-based particles and the positively charged cationic polymer. As a result, it is considered that the coating layer of the cationic polymer covering the silicon-based particles is less likely to collapse, and therefore the exposure of the silicon particles to the electrolyte is suppressed. Therefore, it is considered that the charging and discharging efficiency of a battery using such an electrode material, particularly a non-aqueous lithium ion secondary battery, is less likely to decrease even with repeated charging and discharging. The charging and discharging efficiency after a certain charging and discharging cycle is the ratio of the discharge capacity in the charging and discharging cycle to the initial discharge capacity.

[0017] However, even when a cationic polymer coating layer is used, depending on the type of counter anion possessed by the cationic polymer, the charge / discharge efficiency may be decreased. This is because the surface of the silicon-based particle is negatively charged, and depending on the type of counter anion, the counter anion possessed by the cationic polymer is difficult to approach the silicon-based particle, and therefore the cationic polymer coating layer is not sufficiently formed on the surface of the silicon-based particle.

[0018] In this regard, the decrease in charge / discharge efficiency can be suppressed by using a fluorine-containing anion, such as bis(fluorosulfonyl)imide (FSI) anion or bis(trifluoromethanesulfonyl)imide (TFSI) anion, as the counter anion of the cationic polymer. This is believed to be because the use of a fluorine-containing anion reduces the resistance of the SEI formed on the active material surface during charging.

[0019] The silicon-based active material is preferably sufficiently coated with the cationic polymer, particularly to the extent that the zeta potential is positive in water.

[0020] The silicon-based active material may have a zeta potential in water of more than 0.0 mV and not more than 50.0 mV. The silicon-based active material may have a zeta potential in water of more than 0.0 mV, 1.0 mV or more, 2.0 mV or more, 10.0 mV or more, 20.0 mV or more, or 25.0 mV or more, and may be 50.0 mV or less, 45.0 mV or less, 40.0 mV or less, or 30.0 mV or less.

[0021] The "zeta potential" is also called the electrokinetic potential, and refers to the portion of the potential difference at the interface between a solid and a liquid that effectively affects the electrokinetic phenomenon. In the present disclosure, the zeta potential is the zeta potential measured by the laser Doppler method, which is an electrophoretic light scattering method.

[0022] Silicon-based particles The silicon-based particles may be, for example, Si alloy particles or Si particles. The Si alloy particles may be, for example, an alloy of Si and one or more metals selected from the group consisting of Sn, Ti, Fe, Ni, Cu, Co, and Al.

[0023] <Cationic Polymer> The cationic polymer has a fluorine-containing anion as a counter anion.

[0024] The cationic polymer may be any cationic polymer that has a fluorine-containing anion, has low reactivity with the electrolyte under the conditions of use of the nonaqueous lithium ion secondary battery, and has a positive zeta potential in the electrolyte.

[0025] Specifically, the cationic polymer is preferably at least one selected from the group including poly(diallyl dimethyl chloride), copolymers of poly(diallyl dimethyl chloride) with other polymers, and anion exchange resins, in which all or a part of the counter anion is exchanged with a fluorine-containing anion.

[0026] The fluorine-containing anion may be, for example, an imide-based anion, such as bis(fluorosulfonyl)imide (FSI) anion and bis(trifluoromethanesulfonyl)imide (TFSI) anion.

[0027] The fluorine-containing anion may also be a hexafluorophosphate anion or a tetrafluoroborate anion.

[0028] <Anionic Binder> The electrode material of the present disclosure preferably further contains an anionic binder.

[0029] Since the anionic binder has a negative zeta potential in the electrolyte, a Coulombic interaction occurs between the anionic binder and the silicon-based active material in the electrode mixture of the present disclosure, thereby suppressing the expansion and contraction of the electrode material as a whole during charging and discharging of the battery.

[0030] The anionic binder may be at least one selected from the group including polyacrylic acid, carboxymethyl cellulose, polystyrene sulfonic acid, and poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate).

[0031] Negative electrode body The negative electrode body of the present disclosure contains the electrode material of the present disclosure.

[0032] The negative electrode body has a negative electrode current collector and a negative electrode active material. The negative electrode body may have a shape in which the surface of the negative electrode body, such as a layer or a rod, is partially or entirely covered with a negative electrode active material layer. The negative electrode active material layer contains the electrode material of the present disclosure.

[0033] <Negative electrode active material layer> The negative electrode active material layer can contain the electrode material of the present disclosure, and optionally a conductive assistant and the like.

[0034] The negative electrode active material layer may be formed, for example, by applying and drying a slurry in which the electrode material of the present disclosure and an optional conductive assistant are dispersed on a substrate. The substrate may be made of a conductive material such as a metal, and may also serve as a negative electrode current collector.

[0035] (Conductive assistant) The conductive assistant may be a known one, for example, a carbon material, metal particles, etc. The carbon material may be at least one selected from the group consisting of carbon black such as Ketjen black, acetylene black, furnace black, vapor grown carbon fiber (VGCF), carbon nanotubes, and carbon nanofibers, and from the viewpoint of electronic conductivity, may be at least one selected from the group consisting of VGCF, carbon nanotubes, and carbon nanofibers. The metal particles may be nickel, copper, iron, stainless steel, etc.

[0036] <Negative electrode current collector> The material used for the negative electrode current collector may be stainless steel (SUS), aluminum, copper, nickel, iron, titanium, gold, platinum, zinc, carbon, etc. The negative electrode current collector may be made of these materials with nickel, chromium, carbon, etc. plated or vapor-deposited on the surface. The negative electrode current collector is preferably made of copper or a copper alloy, or made of these materials with nickel, chromium, carbon, etc. plated or vapor-deposited on the surface.

[0037] The shape of the negative electrode current collector is not particularly limited, and may be, for example, a rod shape or a layer shape.

[0038] <Non-aqueous lithium-ion secondary battery> The nonaqueous lithium ion secondary battery of the present disclosure is a nonaqueous lithium ion secondary battery in which a positive electrode body, a separator, and a negative electrode body of the present disclosure are housed in this order in a battery case filled with an electrolyte.

[0039] FIG. 1 is a schematic diagram of a nonaqueous lithium-ion secondary battery 100 according to a first embodiment of the present disclosure.

[0040] 1, a nonaqueous lithium ion secondary battery 100 according to the first embodiment of the present disclosure is housed in a battery case 150 filled with a nonaqueous electrolyte 140, with a positive electrode body 110, a separator 120, and a negative electrode body 130 arranged in this order. Here, the positive electrode body 110 has a shape in which both sides of a positive electrode current collector layer 111 are covered with a positive electrode active material layer 112. In addition, the negative electrode body 130 has a shape in which both sides of a negative electrode current collector layer 131 are covered with a negative electrode active material layer 132.

[0041] <Positive electrode body> The positive electrode body has a positive electrode current collector and a positive electrode active material. The positive electrode body may have a shape in which the surface of a layered or rod-shaped positive electrode body is partially or entirely covered with a layer containing the positive electrode active material, i.e., a positive electrode active material layer.

[0042] The material used for the positive electrode current collector may be any of the materials described for the negative electrode current collector, and among these, the material for the positive electrode current collector is preferably aluminum.

[0043] The shape of the positive electrode current collector layer may also be any of the shapes described for the negative electrode current collector.

[0044] The positive electrode active material layer may contain any positive electrode active material that can be employed in a lithium ion battery.

[0045] Such positive electrode active materials include, for example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, Li 1+x Mn 2-x-y M y The material may be, but is not limited to, a Li-Mn spinel substituted with a different element having a composition represented by O4 (M is one or more metal elements selected from Al, Mg, Co, Fe, Ni, and Zn).

[0046] In addition, such a positive electrode active material may be, for example, a sulfur-based active material. Here, the sulfur-based active material is an active material containing at least S element. The sulfur-based active material may or may not contain Li element. Examples of the sulfur-based active material include elemental sulfur, lithium sulfide (Li2S), and lithium polysulfide (Li2S x , 2≦x≦8).

[0047] <Separator> The separator may be a layer of a porous resin, such as a layer of polypropylene or polyethylene.

[0048] As the separator, a porous polymer membrane such as a porous polyethylene membrane (PE), a porous polypropylene membrane (PP), a porous polyolefin membrane, or a porous polyvinyl chloride membrane can be used. In addition, a lithium ion conductive polymer electrolyte membrane can also be used as the separator. These separators can be used alone or in combination. From the viewpoint of increasing the battery output, it is preferable to use a three-layer coated separator in which a porous polyethylene membrane (PE) is sandwiched between upper and lower layers of porous polypropylene membranes (PP).

[0049] <Negative electrode body> The negative electrode body is the negative electrode body of the present disclosure.

[0050] <Electrolyte> The electrolyte may be a composition in which a supporting salt is contained in a non-aqueous solvent. The non-aqueous solvent may be a material selected from the group consisting of an organic electrolyte, a fluorine-based solvent, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and a combination of two or more of these.

[0051] The non-aqueous solvent is preferably a fluorine-based solvent, such as a fluorinated carbonate ester. Specific examples of the fluorinated carbonate ester include methyl 2,2,2-trifluoroethyl carbonate (MFEC; Carbonic acid, methyl 2,2,2-trifluoroethyl ester; CAS 156783-95-8) and / or difluorodimethyl carbonate (DFDMC), and a mixture of these in a volume ratio of 50:50 is particularly preferred.

[0052] Examples of the supporting salt include materials selected from the group consisting of lithium compounds (lithium salts) of LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiC4F9SO3, LiN(CF3SO2)2, LiC(CF3SO2)3, and LiI, and combinations of two or more of these. From the viewpoints of improving the battery voltage and durability, LiPF6 is preferred as the supporting salt.

[0053] <Battery case> The battery case can be made of a material that is inactive to the non-aqueous electrolyte, such as a resin. EXAMPLES

[0054] Examples 1 to 3 and Comparative Examples 1 and 2 Example 1 Preparation of Si active material particles 1 g of Si particles was dispersed in 1 L of 0.01 M LiFSI (Tokyo Chemical Industry) solution containing 0.01 mass % of cationic polymer poly(diallyldimethylchloride) (Sigma-Aldrich) using a homogenizer and stirred for 1 hour. Here, in the solution, FSI, which is the anion of LiFSI, is partially or completely exchanged with the anion of the cationic polymer.

[0055] The stirred solution was filtered and washed three times with 100 mL of water to remove excess Li salt and polymer. The powder obtained was further vacuum dried at 60°C for 24 hours to obtain Si active material particles coated with cationic polymer.

[0056] The obtained Si active material particles were redispersed in water, and the zeta potential in water was measured using a zeta potential meter, which was +29.6 mV.

[0057] <Preparation of non-aqueous lithium-ion secondary battery> In a screw cap, NMP, a 5% by mass solution of butyl butyrate in PVdF binder, and LiNi with an average particle size of 6 μm as the positive electrode active material were placed. 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and VGCF as a conductive additive were added to a container and stirred for 10 minutes with a mixer (ARE-310, manufactured by Thinky Corporation) to obtain a positive electrode slurry. The positive electrode slurry was applied to an Al foil (manufactured by Showa Denko) as a positive electrode current collector by the blade method using an applicator to form a positive electrode active material layer, and a positive electrode body was produced. The applied positive electrode active material layer was dried on a hot plate at 80°C for 60 minutes.

[0058] Water, SBR as a binder, Si active material particles prepared as the negative electrode active material, VGCF and KB as conductive assistants were added to a screw cap, and the container was stirred for 10 minutes with a foam mixer (ARE-310, manufactured by Thinky Corporation). The mixture was applied to a Cu foil (manufactured by Furukawa Electric Co., Ltd.) as a negative electrode current collector by the blade method using an applicator to form a negative electrode active material layer, and a negative electrode body was produced. The applied negative electrode active material layer was dried on a hot plate at 80°C for 60 minutes.

[0059] The produced positive electrode body and negative electrode body were punched out to φ14 and φ16, respectively, and then set in a roll press machine and pressed at 20 kN / cm. Thereafter, the positive electrode body was vacuum dried at 120°C and the negative electrode body was vacuum dried at 60°C for 24 hours.

[0060] The positive electrode body and the negative electrode body were moved to a glove box, and 1 mL of an electrolyte solution of 1.2 M LiPF6 solution (solvent: FEC:EC:EMC:DMC (1:2:4:3 vol%)) was dropped onto the negative electrode body, a separator (made of PP) was laminated, and 1 mL of electrolyte was again dropped. Then, the positive electrode was laminated, and a coin cell was formed using an automatic coin cell crimping machine (Hosen Co., Ltd.), to prepare a nonaqueous lithium ion secondary battery.

[0061] Example 2 A nonaqueous lithium ion secondary battery of Example 2 was prepared in the same manner as in Example 1, except that the amount of the cationic polymer was 0.06 mass %.

[0062] Example 3 A nonaqueous lithium ion secondary battery of Example 3 was prepared in the same manner as in Example 1, except that a polyacrylic acid-based binder was used as the binder in the production of the negative electrode body.

[0063] Comparative Example 1 A nonaqueous lithium ion secondary battery of Comparative Example 1 was prepared in the same manner as in Example 1, except that Si particles not coated with a cationic polymer were used as the Si active material particles.

[0064] Comparative Example 2 A nonaqueous lithium ion secondary battery of Comparative Example 2 was prepared in the same manner as in Example 1, except that 1 g of Si particles was dispersed in a 1 L solution containing 0.01 mass % of poly(diallyl dimethyl chloride) (Sigma-Aldrich), which is a cationic polymer, using a homogenizer, and the dispersion was stirred for 1 hour to obtain Si active material particles.

[0065] That is, in Comparative Example 2, the counter anion of the cationic polymer was a chloride ion.

[0066] <Measurement of charge / discharge efficiency> The nonaqueous lithium ion secondary batteries of each example thus produced were charged at a constant current of 0.1 C rate to 4.2 V, and then discharged at a rate of 0.1 C to 2.5 V, and the battery capacity was determined as the initial discharge capacity. Next, a charge-discharge test was performed 50 times, in which a constant current was charged at a rate of 1 C to 4.2 V, and then a constant current was discharged at 1 C, and the ratio (%) of the discharge capacity for each cycle to the initial discharge capacity, i.e., the charge-discharge efficiency, was determined, and the average value was calculated.

[0067] <result> For each example of the nonaqueous lithium ion secondary battery, the manufacturing conditions, i.e., the presence or absence of a cationic polymer, the type of counter anion, the zeta potential (mV) of the Si active material particles in water, and the type of binder used in the negative electrode body, as well as the results, i.e., the average charge / discharge efficiency (%), are shown in Table 1.

[0068] [Table 1]

[0069] As shown in Table 1, in Examples 1 to 3 in which a cationic polymer having a counter anion of FSI was used, the average charge / discharge efficiency (%) was 97.0%, 98.3%, and 98.1%, respectively. In contrast, in Comparative Example 1 in which Si particles not coated with a cationic polymer were used as the Si active material particles, and Comparative Example 2 in which a cationic polymer having a counter anion of chloride ion was used, the average charge / discharge efficiency (%) was 96.3% and 95.5%, respectively. [Explanation of symbols]

[0070] 100 Non-aqueous lithium-ion secondary battery 110 Positive electrode body 111 Positive electrode current collector layer 112 Cathode active material layer 120 Separator 130 Negative electrode body 131 Negative electrode current collector layer 132 Negative electrode active material layer 140 Nonaqueous electrolyte 150 Battery Case

Claims

1. The silicon-based active material includes silicon-based particles at least partially coated with a cationic polymer, The cationic polymer has a fluorine-containing anion as a counter anion, and The silicon-based active material has a positive zeta potential in water. electrode material.

2. The electrode material according to claim 1 , wherein the silicon-based particles are Si particles or Si alloy particles.

3. 3. The electrode material according to claim 1, wherein the cationic polymer is at least one selected from the group consisting of poly(diallyl dimethyl chloride), a copolymer of poly(diallyl dimethyl chloride) with another polymer, and an anion exchange resin, in which all or a part of the counter anion is exchanged with the fluorine-containing anion.

4. The electrode material according to any one of claims 1 to 3, wherein the fluorine-containing anion is an imide-based anion.

5. The electrode material according to any one of claims 1 to 4, further comprising an anionic binder.

6. 6. The electrode material according to claim 5, wherein the anionic binder is at least one selected from the group consisting of polyacrylic acid, carboxymethyl cellulose, polystyrene sulfonic acid, and poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate).

7. A negative electrode body comprising the electrode material according to any one of claims 1 to 6.

8. A non-aqueous lithium ion secondary battery comprising a positive electrode body, a separator, and the negative electrode body according to claim 7 housed in this order in a battery case filled with an electrolyte.

Citation Information

Patent Citations

  • Negative electrode for nonaqueous secondary battery and manufacture of the same, and nonaqueous secondary battery

    JP2014165007A

  • Negative electrode active material for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

    JP2016028383A

  • Silicon material-carbon layer-cationic polymer layer complex

    JP2016048628A

  • Juicer

    WO2013075409A1